Social learning and principal-agent problems in profit sharing contract. Issue 4 (14th November 2016) - Sapuan, Noraina Mazuin; Sanusi, Nur Azura; Ismail, Abdul Ghafar; Wibowo, Antoni
Abstract : Purpose: The purposes of this study are twofold. First, to theoretically examine the profit-sharing (mudarabah) contract that produces an optimal distribution of return in the presence of social learning (shuratic process) within the environment of asymmetric information. Second, to empirically investigate the optimal condition of profit-sharing ratio (PSR) and social learning for profit-sharing (mudarabah) contract in Islamic banking. Design/methodology/approach: Data from one of the biggest and earliest Islamic banks in Malaysia were taken as a proxy of an Islamic bank. The data are collected from the period of 2009 to 2013, and these will be used for the simulation process by using the genetic algorithm (GA) technique. Findings: The empirical results discovered that Islamic banks had used social learning in their daily activities, especially in the asset side. The results also showed that the trend of social learning has a positive relationship with the trend of Islamic banks' net profit. Additionally, the results also indicated that the Islamic banks' net profit has a positive relationship with its PSR from the profit-sharing (mudarabah) financing and securities investment. Originality/value: This study is the first of its kind that investigates the implementation of the social learning process in Islamic banking operation. This study also used the latest technique from artificial intelligence system, i.e. a GA, to attain an optimal value for PSR and social learning process.